Droga jako przykład biblijnych wyrazów–kluczy - Lewicka, Katarzyna (Acta Universitatis Lodziensis. Folia Linguistica, 2005)
The article discusses the metaphor of the road in the Polish translation of the Bible. We notice 2 parts: one, theoretica, concerning the matter of metaphor and the other, analytical, concentrating on the semantic differentiation of the lexeme road.Within this part we can enumerate the following aspects: the road in the sense of space or time, the road as a way leading somewhere, the road as something we set out ou, the road as a measure of distance and time, the metaphoric sense of the lexeme road.The author also points out that the lexeme road correlates to other parts of speech, creating biblically – derived phraseology.